2018
DOI: 10.14260/jemds/2018/301
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia in CKD Patients and Its Correlation With Severity of Renal Dysfunction

Abstract: BACKGROUND Chronic kidney disease (CKD) is a significant global health problem with significant morbidity and mortality. Dyslipidaemia along with an abnormal apolipoprotein profile and composition is a common complication associated with the decline in eGFR in CKD. The association between abnormal lipid profile and severity of CKD has rarely been studied in a general population, especially in Indian setup and may have a future prognostic and management implication in patients with CKD. Aims and Objectives-To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
3
0
0
Order By: Relevance
“…On comparing various parameters between cases and controls, there is a significant rise in blood Urea (p<0.001**) and serum Creatinine (p<0.001**). Mohanty et al study also showed similar significant statistical association of total cholesterol (p= 0.001), triglyceride (p= 0.001), HDL (p= 0.000), LDL (p= 0.000) between control and cases [25]. Kumari et al study also found similar results to our study [32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On comparing various parameters between cases and controls, there is a significant rise in blood Urea (p<0.001**) and serum Creatinine (p<0.001**). Mohanty et al study also showed similar significant statistical association of total cholesterol (p= 0.001), triglyceride (p= 0.001), HDL (p= 0.000), LDL (p= 0.000) between control and cases [25]. Kumari et al study also found similar results to our study [32].…”
Section: Discussionsupporting
confidence: 89%
“…Mean age of cases was 56.66±12.22 y and control was 41.05±17.75 y. This was similar to that of CKD Registry of India 2007 [21] where the mean age of cases was 48.3±16.6 y and in the studies by Patel and Sirajwala et al [24] and by Mohanty et al [25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation